Evaluation of interleukin-6 and tumor necrosis factor-alpha in tears and serum and its associated factors in age related macular degeneration patients - Rosli, Abdul Hadi (2021)
Introduction: Age-Related Macular Degeneration (AMD) is a progressive neurodegenerative disease that affect the macula lutea. AMD is the leading cause of irreversible central vision loss in elderly population in developed countries. AMD is a multifactorial disease. The development of AMD involve continuous interaction between genetic factors, oxidative stress and environmental factors. Recent studies has been showing that inflammation plays a critical role in pathogenesis of AMD. Increased in Interleukin-6 (IL-6) and Tumor necrosis factor alpha (TNF-α) in the serum and intraocular fluid has been associated with AMD and its progression. Measurement of IL-6 and TNF-α in tears will provide a potential non-invasive biomarker for the progression and monitoring of AMD. Objectives: Our objective was to evaluate IL-6 and TNF-α in tears and serum between AMD patients and Control group as well as between Early AMD and Late AMD. Our objective also was to determine the association between IL-6 and TNF-α in tears with duration of AMD, serum level of IL-6 and TNF-α, smoking status and AMD status. Methods: A comparative cross-sectional study was conducted at a tertiary hospital in Malaysia, Hospital Universiti Sains Malaysia (USM) from June 2018 till May 2021. This study involved patients with Early AMD, Late AMD and Control group who attended Ophthalmology Clinic. Tears and serum samples were collected. The samples were analysed using commercial Human IL-6 and TNF-α ELISA kit to measure IL-6 and TNF-α levels in tears and serum. Statistical analysis was done using SPSS Inc Version 24. Results: A total of 142 patients (56 early AMD, 56 late AMD and 30 Control group) were recruited and analysed in this study. In the late AMD group, there was no late dry AMD and only include late neovascular AMD (nAMD). The adjusted mean for IL-6 in tears was significantly higher in AMD compared to Control group (21.91 (95%CI: 19.89, 23.93) vs 16.27 (95%CI: 12.32, 20.22), respectively, p= 0.014) after adjusted with covariates. The adjusted mean for IL-6 in serum also was significantly higher in AMD compared to Control group (12.01 (95%CI: 10.93, 13.08) vs 8.51 (95%CI: 6.41, 10.62), respectively, p= 0.004) after adjusted with covariates. The adjusted mean IL-6 in serum was significantly higher in Late nAMD compared to Early AMD (13.97 (95%CI: 12.43, 15.52) vs 10.03 (95%CI: 8.49, 11.58), respectively, p= 0.001) after adjusted with covariates. The adjusted mean TNF-α in serum was significantly higher in AMD compared to Control group (18.49 (95%CI: 17.11, 19.86) versus 13.96 (95%CI: 11.27, 16.65), respectively, p= 0.004) after adjusted with covariates. There was no significant association found between IL-6 and TNF-α level in tears with duration of AMD, serum level of IL-6 and TNF-α, smoking status and AMD status. Conclusion: Systemic IL-6 level was significantly higher in Late nAMD. There was no different in the level of IL-6 and TNF-α in tears between Early AMD and Late nAMD. There was also no significant factors associated with IL-6 and TNF-α in tears among AMD patients. A large cohort study is needed for further evaluation of tears inflammatory biomarkers level in AMD patients.